Penerapan Metode AHP-TOPSIS Untuk Penyeleksian Permohonan Kredit Pada Koperasi Pegawai Republik Indonesia - Gani, Hilmansyah; Suseno, Jatmiko Indro (Universitas Diponegoro, 2015)
In this study discusses the selection of a decision support system of credit proposals, which make loans to members of the Cooperative Republic of Indonesia ( KPRI ) savings and loan. Decision support system used to aid managers in determining which members are entitled to be given a loan. Errors in granting loans to members of the cooperative will menyebebakan loss or bad credit cooperatives. The method used in this study are TOPSIS ( Technique Order Preference by Similarity to Ideal Solution ) and AHP ( Analytical Hierarchy Process ). TOPSIS is used for ranking members of the cooperative are given a loan, while the AHP is used for the weighting of the criteria used in TOPSIS. The results of this study is an application or software that can menentukkan members who make loans based on lending criteria, large installment, destination, length installment, the basic salary, the last member status, previous loans, and deposits. So that these applications can provide a solution for managers in selecting members to be given credit loans.